1997
DOI: 10.1177/112067219700700207
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Retinopathy and Cerebral Hemodynamic Impairment in Type II Diabetes

Abstract: These findings seem to confirm the hypothesis of a silent cerebral microangiopathy affecting diabetic patients, with concomitant signs of microangiopathic damage in other districts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 22 publications
3
20
0
Order By: Relevance
“…The PI of the MCA and ICA was increased only in complicated patients, whereas the PI in noncomplicated patients was comparable to that in control subjects. These results were quite consistent with those of Lippera et al 20 They demonstrated significantly increased pulsatility of the MCA in diabetic patients with retinopathy compared with those without retinopathy. However, most of their patients were hypertensive, and long-standing hypertension could also increase the pulsatility of the MCA and ICA, 32 as well as reduce cerebrovascular reactivity.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The PI of the MCA and ICA was increased only in complicated patients, whereas the PI in noncomplicated patients was comparable to that in control subjects. These results were quite consistent with those of Lippera et al 20 They demonstrated significantly increased pulsatility of the MCA in diabetic patients with retinopathy compared with those without retinopathy. However, most of their patients were hypertensive, and long-standing hypertension could also increase the pulsatility of the MCA and ICA, 32 as well as reduce cerebrovascular reactivity.…”
Section: Discussionsupporting
confidence: 83%
“…However, only a few studies have been performed in patients with DM. By using TCD, Lippera et al 20 demonstrated increased pulsatility and reduced cerebrovascular reactivity of the middle cerebral artery (MCA) in diabetic patients with retinopathy, but the effect of hypertension, a major factor also influencing cerebral hemodynamics, was not excluded. Fulesdi et al 21 also demonstrated a decrease of cerebrovascular reactivity of the MCA in normotensive patients with long-term type 1 DM.…”
mentioning
confidence: 99%
“…In patients with DM1, CVR has been shown to be decreased in patients with a long (>10–15 years) disease duration [3] and in those with autonomic neuropathy [4, 5]. Previous studies in DM2 patients have shown similar results, mostly reporting impaired CVR only in selected subgroups of patients with advanced complications or a long disease duration [6,7,8,9]. These findings may not be representative of the general DM2 population.…”
Section: Introductionsupporting
confidence: 64%
“…12,13,25 CVR appears to be reduced in patients with long-term insulindependent diabetes 11 and in those with proliferative diabetic retinopathy. 26 Furthermore, vasomotor tone appears to be increased in severe, noncontrolled hypertensives as compared with controlled hypertensives and normotensive subjects, and an inverse association was found between ACZ-CVR and the degree of echocardiographic left atrial enlargement. 12 CVR has also been noted to be markedly decreased in cerebrovascular diseases, especially in patients with large-vessel occlusive disease.…”
Section: Discussionmentioning
confidence: 99%